2014
DOI: 10.4172/2155-9538.1000128
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Brain Signal Monitoring Technologies for BCI Applications: Challenges and Prospects

Abstract: Significant strides have been made since 1940s for monitoring brain activities and utilizing the information for diagnosis, therapy, and control of robotic instruments including prosthetics. Monitoring brain activities with brain computer interfacing (BCI) technologies are of recent interest to due to the immense potential for various medical applications, particularly for many neurological disorder patients, and the emergence of technologies suitable for long duration BCI applications. Recent initiatives are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 101 publications
(146 reference statements)
2
18
0
Order By: Relevance
“…At the other extreme, noninvasive scalp electrodes are used to obtain electroencepha-logram (EEG). Between these extremes lies the electrocorticogram (ECoG), typically obtained by placing macroelectrodes on the surface of the brain, widely used in epileptic patients to find the seizure focus (Lesser et al, 2010;Morshed and Khan, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the other extreme, noninvasive scalp electrodes are used to obtain electroencepha-logram (EEG). Between these extremes lies the electrocorticogram (ECoG), typically obtained by placing macroelectrodes on the surface of the brain, widely used in epileptic patients to find the seizure focus (Lesser et al, 2010;Morshed and Khan, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The headset can measure brainwave signals safely and easily and its Sky ThinkGear ASIC chip has been designed for health and wellness, as well as educational and popular EEG technology use. (31) According to the international 10-20 system, the NeuroSky headset is designed for use in position Fp1 to retrieve EEG signals. Position A1 is the reference ground (as shown in Fig.…”
Section: Dwt Analysis Of Eeg Signalsmentioning
confidence: 99%
“…In addition, invasive BCI research [ 3 , 4 ] has shown straightforward advances in medicine, which can lead to innovations in BCI that are important for human beings in the future, together with other modern sciences, such as artificial intelligence and robotics. An electroencephalogram-based BCI is a non-invasive technique [ 5 ] that receives brain signals from the scalp to measure the electrical potential of the brain and converts it into commands to control electrical devices, computers, or machines without motor functions [ 6 , 7 ]. BCI systems are used in medical applications [ 8 ], such as diagnosis [ 9 , 10 , 11 , 12 ], treatment [ 13 , 14 ], and rehabilitation [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%